Ethane-oxidising archaea couple CO2 generation to F420 reduction - Olivier N. Lemaire; Gunter Wegener; Tristan Wagner (Nature Communications)
Abstract The anaerobic oxidation of alkanes is a microbial process that mitigates the flux of hydrocarbon seeps into the oceans. In marine archaea, the process depends on sulphate-reducing bacterial partners to exhaust electrons, and it is generally assumed that the archaeal CO2-forming enzymes (CO dehydrogenase and formylmethanofuran dehydrogenase) are coupled to ferredoxin reduction. Here, we study the molecular basis of the CO2-generating steps of anaerobic ethane oxidation by characterising native enzymes of the thermophile Candidatus Ethanoperedens thermophilum obtained from microbial enrichment. We perform biochemical assays and solve crystal structures of the CO dehydrogenase and formylmethanofuran dehydrogenase complexes, showing that both enzymes deliver electrons to the F420 cofactor. Both multi-metalloenzyme harbour electronic bridges connecting CO and formylmethanofuran oxidation centres to a bound flavin-dependent F420 reductase. Accordingly, both systems exhibit robust coupled F420-reductase activities, which are not detected in the cell extract of related methanogens and anaerobic methane oxidisers. Based on the crystal structures, enzymatic activities, and metagenome mining, we propose a model in which the catabolic oxidising steps would wire electron delivery to F420 in this organism. Via this specific adaptation, the indirect electron transfer from reduced F420 to the sulphate-reducing partner would fuel energy conservation and represent the driving force of ethanotrophy.